Articular cartilage restoration in load-bearing osteochondral defects by implantation of autologous chondrocyte-fibrin constructs: an experimental study in sheep - Sha'ban, Munirah; Osman Cassim, Samsudin; Chen, Hui Cheng; S. H., Sharifah Salmah; Saim, Aminuddin; Idrus, Ruszymah (The Journal of Bone and Joint Surgery, 2007)
Ovine articular chondrocytes were isolated from cartilage biopsy and culture expanded in vitro. Approximately 30 million cells per ml of cultured chondrocytes were incorporated with autologous plasma-derived fibrin to form a three-dimensional construct. Fullthickness punch hole defects were created in the lateral and medial femoral condyles. The defects were implanted with either an autologous ‘chondrocyte-fibrin’ construct (ACFC), autologous chondrocytes (ACI) or fibrin blanks (AF) as controls. Animals were killed after 12 weeks. The gross appearance of the treated defects was inspected and photographed. The repaired tissues were studied histologically and by scanning electron microscopy analysis. All defects were assessed using the International Cartilage Repair Society (ICRS) classification. Those treated with ACFC, ACI and AF exhibited median scores which correspond to a nearly-normal appearance. On the basis of the modified O’Driscoll histological scoring scale, ACFC implantation significantly enhanced cartilage repair compared to ACI and AF. Using scanning electron microscopy, ACFC and ACI showed characteristic organisation of chondrocytes and matrices, which were relatively similar to the surrounding adjacent cartilage. Implantation of ACFC resulted in superior hyaline-like cartilage regeneration when compared with ACI. If this result is applicable to humans, a better outcome would be obtained than by using conventional ACI.